Studi Kinerja Rumah Sakit Berbasi Balance Scored (Studi Kualitatif di RSUD Kota Madiun di Lingkungan Manajemen) - Dewi Ridhosari; Ratna Wardani (Jurnal Imejing Diagnostik (JImeD), 2022)
Background: Organizational performance is something produced by an organization in a certain period with reference to established standards. Management performance measurement aims at work efficiency using balanced score card (BSC), which is a performance measurement solution. BSC consists of two  dimensions: financial and non-financial dimensions. The purpose of the study was to describe the measurement of the performance of the Madiun City general hospital using the Balance Scorecard method.Methods: Research design uses qualitative descriptive methods. The selection of informants was obtained from observations and interviews to employees of the Madiun Citygeneral hospital with 7 respondent. This study used purposive sampling techniques. Research instruments with observation sheets, interview guidelines and documentation studysheets.Results: The results of the study at the general hospital in Madiun City area showed that financial performance was considered good, the achievement of customer satisfaction levels in 2020 was quite good, the perspective of internal business processes could not be achieved at standard numbers due to the Covid-19 pandemic, the achievement of employee satisfaction levels in the good category even though there were 3 elements that were considered less good.Conclusions: The results of the research conducted are expected by the hospital should use performance assessment based on the concept of balance score card to implement and integrate the strategic planning of the hospital. Hospitals also need to improve employee capabilities by providing training to employees in turns, or organizing inhouse training to save costs. The perspective of benefit performance is that the poor must be served in Madiun City Hospital.